Quality of Life in Patients with Chronic Kidney Disease Managed with or without Dialysis: An Observational Study. Issue 11 (24th November 2022) - So, Sarah; Li, Kelly; Hoffman, Anna T.; Josland, Elizabeth; Brown, Mark A.
Key Points: Patients on conservative kidney management reported no significant decline in quality of life domains at 12 months or in quality of life scores at 18 months. Appropriately supported patients on conservative kidney management can maintain quality of life. Visual Abstract: Abstract : Background: Emerging research suggests that quality of life (QOL) outcomes, such as maintenance of independence, rather than length of life, are the main priority for many patients with end stage kidney disease (ESKD). There is therefore a need to focus on whether QOL for older patients on dialysis differs significantly from conservative kidney management (CKM). This study aimed to describe the QOL trajectory for patients with ESKD, comparing CKM to dialysis and transplantation. Methods: This retrospective, observational study included all patients who attended the Kidney Supportive Care Clinic at St. George Hospital and had one or more EuroQOL (EQ5D5L) questionnaires between July 2014 and May 2020. Kruskal–Wallis tests compared QOL scores between groups at baseline and 12 months. Wilcoxon signed rank tests compared QOL scores from baseline to 18 months within groups. Chi-squared tests compared proportions of patients reporting problems with QOL "domains" between the groups at baseline and 12 months. McNemar's tests compared changes in proportions of patients reporting problems with QOL "domains" within groups from baseline to 12 months. Results: A total of 604 patients had an initial survey. At baseline, patients who were managed conservatively reported more problems with mobility, self-care, and ability to perform usual activities. However, pain/discomfort and anxiety/depression were no higher in the conservative population. CKM patients reported no significant decline in mobility, self-care, ability to perform their usual activities, pain/discomfort, or anxiety/depression after 12 months or in QOL scores after 18 months compared with the other groups. Conclusions: QOL scores or symptom burdens did not change significantly in patients receiving CKM compared with dialysis, suggesting that appropriately supported CKM can maintain patients' QOL.